Anesthesia for pregnant women with pulmonary hypertension. Issue 3 (June 2016) - Rex, Steffen; Devroe, Sarah
Abstract : Purpose of review: Purpose of review is to summarize and highlight recent advances in the management of pregnant patients with pulmonary hypertension. Recent findings: Despite recent advances in the therapy of pulmonary hypertension, prognosis for pregnant patients with pulmonary hypertension remains poor with high maternal mortality. Pregnancy is still considered contraindicated in these patients. If pregnancy occurs, referral to a tertiary hospital and a multidisciplinary approach ensure the best possible outcome. All pregnant patients with pulmonary hypertension should be counseled for a termination of pregnancy. If the patient wants to continue the pregnancy despite strong recommendations for therapeutic interruption, specific pulmonary hypertension therapy has to be initiated, adjusted, and/or augmented. A close clinical follow-up of the mother throughout the entire pregnancy is of utmost importance. Elective caesarean section in week 34–36 is recommended as preferred mode of delivery, preferentially under epidural or low-dose combined spinal-epidural anesthesia. Because of an acute increase in pulmonary vascular resistance and delivery-associated acute volume overload, the immediate postpartum period carries the highest risk for acute right ventricular failure necessitating close monitoring and treatment on an ICU. Summary: Anesthesiologists involved in the management of pregnant patients with pulmonary hypertension must have detailed knowledge of pathophysiological alterations in pregnancy and during birth, cardiac (patho)physiology, cardiovascular and obstetric pharmacology, hemodynamic monitoring, and echocardiography. Both regional and general anesthesia have typical adverse effects that can severely jeopardize the cardiovascular system in patients with pulmonary hypertension, and should therefore be anticipated/prevented/rapidly treated by the attending anesthesiologist.